The implications of Adverse Childhood Experience (ACE) exposure for juvenile violent offending and homicide: an extension of prospective prediction of juvenile homicide/attempted homicide - Baglivio, Michael T. (The Routledge international handbook of juvenile homicide, 2024)
Approximately 7% of US murders involve a juvenile perpetrator, with less than 10% of those perpetrators being females. This chapter provides demographic information (sex, age, race/ethnicity) of all juvenile homicide/attempted homicide delinquency referrals across the state of Florida since the early 1990s through mid-2021. Further, prevalence of prominent risk factors and indicators of childhood abuse, neglect, and household dysfunction, as well as cumulative trauma measured per an adverse childhood experiences (ACE) score, are examined for those homicides/attempted homicides occurring since 2007 (the implementation of a standardized risk/need assessment). While correlates are informative, unfortunately, few studies have prospectively examined the predictors of future juvenile homicide offending, with limited work predicting first-time murder among a sample of prior adjudicated male and female youth. This chapter extends prior prediction of homicide among adjudicated youth, examining 7 years (exceeding the 2 years in prior study) of youth first referred under age 13 to prospectively predict a referral for homicide/attempted homicide by the age of 18. Results indicate those early-onset justice-involved youth who later commit homicide by age 18 were more likely male and Black, had more instances of running away, evidenced more extensive anger/aggression issues, and lived in areas of greater social disorganization at their first arrest (by age 13). We therefore add to the scant literature on the predictors of future juvenile homicide among youth involved in the justice system, and discuss potential avenues for intervention.